2019
DOI: 10.1021/acs.jpcc.8b11044
|View full text |Cite
|
Sign up to set email alerts
|

Improved Transport Properties and Novel Li Diffusion Dynamics in van der Waals C2N/Graphene Heterostructure as Anode Materials for Lithium-Ion Batteries: A First-Principles Investigation

Abstract: In this paper, we report a theoretical investigation of the electronic structures, electron/phonon transport properties, and electrochemical parameters of the C2N/graphene bilayer. The p-type C2N/graphene bilayer, with a direct band gap of 0.2 eV at Γ-point, exhibits promising electric conductivity similar to that of the graphene monolayer. In addition, it also shows excellent lattice thermal conductivity of 1791.1 W/m·K, compared to 82.22 W/m·K of the C2N monolayer. The theoretical capacity of C2N/graphene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 87 publications
(165 reference statements)
2
28
0
Order By: Relevance
“…The structures of different compositions of the bilayer heterostructures are presented in Fig. 9 b, c. [ 38 ]. Guo et al [ 64 ] and Lin et al [ 65 ] also reported a DFT study on C 3 N/phosphorene heterostructure for LIBs, while Bao et al explored its potential for Li/Na battery.…”
Section: Dft-guided Studies Of Cnbms For Energy Storage Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The structures of different compositions of the bilayer heterostructures are presented in Fig. 9 b, c. [ 38 ]. Guo et al [ 64 ] and Lin et al [ 65 ] also reported a DFT study on C 3 N/phosphorene heterostructure for LIBs, while Bao et al explored its potential for Li/Na battery.…”
Section: Dft-guided Studies Of Cnbms For Energy Storage Devicesmentioning
confidence: 99%
“…Reproduced with permission from Ref. [ 38 ]. d Top and side views of the Li adsorption site on the C 3 N/P heterostructure (Li/C 3 N/P, C 3 N/Li/P, and C 3 N/P/Li).…”
Section: Dft-guided Studies Of Cnbms For Energy Storage Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…It shows a high theoretical capacity ~1400 mAh/g and high energy density for lithiation and fast charge and discharge rate. Rao et al studied in detail the monolayer of C 2 N and the bilayer heterostructure of C 2 N/graphene [45]. Their results show that the diffusion coefficient for the heterostructure was better than the monolayer after the diffusion of lithium, whereas the capacity of monolayer was 220% the bilayered heterostructure.…”
Section: Heterostructures Of 2d Compounds With Graphenementioning
confidence: 99%